Crafting creativity & creating craft - Weida, Courtney Lee (Advances in Creativity and Giftedness ;, 2014)
This nine chapter volume explores creativity in art teaching through contemporary craft. A variety of artists, educators and historians share with readers their wealth of practical resources and frameworks for utilizing craft media (fiber, ceramics, baskets, needlepoint, knitting, etc.) and craft approaches (grassroots projects, digital communities, craftivism, etc.) within contemporary K-12 art education, museum and community programming, and teaching artist residencies. Authors representing a variety of specialties in craft, art, and education examine the resurgence of the handmade and homemade in contemporary youth culture, digital implications of how we define and teach craft creatively, and the overlap of design, function, and beauty in artists' work. The anthology also describes the challenges and potentialities of working with craft in education settings, including the overarching craft of teaching practices. Each chapter provides a range of creative frameworks and practical models that educators can use comprehensively: from dynamic digital resources, to community groups, and lesson plans and activities in craft with art classes and special needs classes. The book serves to propose a working definition and rationale of the functions of craft in daily life, popular and youth culture, and larger social issues (including craft, D.I.Y., and activism/"craftivism").